DECELLULARIZATION AND CHARACTERIZATION OF RABBIT HEART - Seitzhaparova, Banu (School of Engineering and Digital Sciences, 2023)
In conformity with the "Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan", from 2010 to 2020, the incidence of cardiovascular diseases (CVD) increased by 44%. According to the Global Burden of Disease (GBD) Study 2019, the global trend of CVD cases doubled (51,8%) between 1990 and 2019. Despite new approaches in the treatment of CVD such as percutaneous coronary intervention (PCI), coronary artery bypass graft (CABG), and left ventricular assist devices (LVAD), which cannot fully compensate for the effectiveness of the original heart, heart transplantation remains as the most effective solution. A growing body of literature recognizes the importance of developing a whole heart constructed from living tissues to provide an alternative option for patients suffering from diseases of the cardiovascular system. A potential solution that shows promise is to generate cell-free scaffolds using heart tissue to be later populated with induced pluripotent or embryonic stem cells and implanted. This study reports the initial phase, i.e., decellularization, in the creation of the whole heart scaffold. The hearts harvested from rabbits were decellularized using a perfusion method. The final bioartificial scaffolds were characterized for the efficiency of decellularization in terms of DNA content, collagen, and glycosaminoglycan (GAG). Findings revealed that the DNA content of the decellularized hearts was significantly reduced while keeping collagen and GAG content unchanged. Decellularized hearts have significant importance in treating CVD as they serve as bioartificial hearts, providing a more clinically relevant model for potential human use. Future work will focus on the recellularization of the heart using induced pluripotent or embryonic stem cells, which allows for a deeper analysis of the effectiveness and prospects of this treatment method.
Keywords: type of access: open access; tissue engineering; whole organ scaffold; extracellular matrix; cardiovascular system; heart decellularization; perfusion; DNA; collagen; GAG